Bridging Law in Books and Law in Action: Ethnographic Insights into Indonesia’s Legal Pluralism - Lode Wijk Pandapotan Girsang; Noviana Simbolon; Nurcahaya Lubis (Universitas Sumatera Utara, 2026)
The dominance of normative‑positivist approaches in Indonesian legal scholarship creates a persistent gap between “law on the books” and everyday legal practice. This scoping review contributes new insight by showing how ethnography functions as a methodological bridge to understand legal pluralism as lived interaction among state, customary, and religious orders. Drawing on a systematic search of Scopus, JSTOR, and Google Scholar (2020–2025), 78 publications were identified and 10 ethnographic studies were synthesized using PRISMA. Ethnographic methods—immersion, in‑depth interviewing, document analysis, and network‑sensitive observation—reveal dynamics that doctrinal analysis overlooks: hybridization of norms, strategic forum navigation, and locally grounded bases of authority and legitimacy. Three advances are offered: (1) an integrated analytical lens combining interpretive anthropology, practice theory, and critical legal pluralism; (2) a mapping of power and agency in plural arenas, including elite capture and marginalization; and (3) attention to methodological innovations (e.g., meta‑ethnography and social‑network–informed approaches). Implications include context‑sensitive policymaking, strengthened access to justice, and more inclusive dispute‑resolution design.